Features of chronic heart failure depending on the left ventricular ejection fraction - A. G. Dushina; E. A. Lopina; R. A. Libis (Российский кардиологический журнал)
Aim. To assess clinical and demographic data, structural and functional features of the myocardium in patients with chronic heart failure (CHF) with a preserved ejection fraction in comparison with patients with CHF with an intermediate (CHF-inEF) and a reduced ejection fraction (CHF-rEF).Material and methods. The study included 186 patients with CHF I-IIB stages, I-III functional classes. One hundred and three patients had a preserved ejection fraction (EF) (≥50%), 43 — intermediate (40-49%) and 40 — reduced (<40%). All patients underwent a comprehensive clinical examination, as well as standard echocardiography.Results. Among patients with CHF-rEF, remodeling of the left ventricular myocardium by the type of concentric hypertrophy was more often observed (69,9%), and among CHF-inEF and CHF-nEF patients — by the type of eccentric hypertrophy (88,4 and 875%, respectively). Restrictive diastolic dysfunction was observed in 2,0% of patients with CHF-rEF and in 21,7% of patients with EF less than 50%.Conclusion. The severity of the clinical course of CHF does not depend on the left ventricular EF. Epidemiology and etiology of CHF-rEF has fundamental differences from CHF-inEF and CHF-nEF: CHF-rEF is more common among women over 60 years old with arterial hypertension and obesity. For patients with CHF-inFV, myocardial remodeling by the type of concentric hypertrophy and the prevalence of non-restrictive types of diastolic dysfunction are characteristic.